The mortality rate after hospital discharge in patients with myelomeningocele decreased after implementation of mandatory flour fortification with folic acid - Salomão, Renato Manganelli; Cervante, Tatiana Protzenko; Salomão, José Francisco Manganelli; Leon, Soniza Vieira Alves (Arquivos de Neuro-Psiquiatria, 2017)
To evaluate the mandatory folic acid fortification of flour on mortality rates after the hospital discharge of children born with myelomeningocele, the most affected age group and the most frequent cause of death.A retrospective study of 383 children born with myelomeningocele from January 1990 to December 2013 in a high-fetal-risk reference hospital.A total of 39 patients died (10.1%),of which 23 (6%) died after discharge. Most children who died were younger than 12 months of age. The most frequent cause of death was infection of the central nervous system, followed by urinary tract sepsis and infections of the respiratory system. Symptomatic Chiari II malformation was the most frequent comorbidity factor.Although there was no significant difference in infant mortality before and after folic acid fortification, there was a significant reduction in deaths after hospital discharge in babies born after implementation of mandatory folic acid fortification
Keywords: meningomyelocele; mortality; folic acid